Inhibition of Chikungunya virus nsP2 protease in vitro by scorpion venom peptide pantinin-1 - Mohammadamin Mastalipour; Mônika Aparecida Coronado; Jorge Enrique Hernández González; Dieter Willbold; Raphael Josef Eberle (PLoS ONE, 2026)
Climate change has facilitated the spread of arboviruses like the Chikungunya virus (CHIKV). CHIKV, a re-emerging virus from the Togaviridae family, has caused numerous global outbreaks. The absence of antiviral therapy against CHIKV poses a significant threat to public health. The cleavage of the viral polyprotein relies on the catalytic activity of nsP2, crucial for viral replication. Therefore the nsP2 protease presents a promising target for antiviral drug development. Animal venom-derived peptides demonstrated potential in combating various diseases including infections, cancer, and neurodegenerative disorders. In this study, we assessed the inhibitory effects of pantinin-1, a peptide derived from the scorpion Pandinus imperator with broad antimicrobial activity, against CHIKV nsP2 protease. Pantinin-1 effectively inhibited CHIKV nsP2 protease, with a half-maximal inhibitory concentration (IC₅₀) of 6.4 ± 2.04 µM and complete inhibition at 175 µM. Further examination revealed that pantinin-1 functions as a competitive inhibitor with low micromolar affinity and exhibited no toxicity up to 20 µM in cell culture. Using docking and molecular dynamics simulations, the protein-peptide interaction was analyzed, and the key residues involved in the protease binding were predicted. These findings underscore the potential of pantinin-1 as a lead candidate targeting nsP2 protease.